Розробка адаптивного чат-бота для аналізу метеорологічних даних і підтримки прийняття рішень у сфері агробізнесу - Альохіна, Дарія Андріївна (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Мета роботи: створення чат-бота для надання суб’єктам аграрного сектору метеопрогнозів і рекомендацій для оптимізації агропроцесів. Об’єкт дослідження: адаптивні чат-боти на основі ШІ. Предмет дослідження: методи аналізу метеоданих і NLP для адаптивних систем. Методи: теоретичний аналіз, моделювання машинного навчання, тестування. Розроблено чат-бот на Python із модулями NLP (BERT), аналізу даних (Pandas, scikit-learn) і адаптації (K-Means), інтегрований із Telegram і OpenWeatherMap. Точність обробки запитів - 95%, зручність - 4.2/5, час реакції - 1.5 с. Наукова новизна: інтеграція NLP і кластеризації для персоналізації в агробізнесі. Практична значущість: оптимізація посіву, поливу, зниження ризиків. Перспективи: інтеграція WeatherAPI, голосовий ввід, агрономічна база.

Objective: To develop a chatbot that provides farmers with weather forecasts and recommendations to optimize agricultural processes. Research Object: Adaptive chatbots based on artificial intelligence. Research Subject: Methods of meteorological data analysis and natural language processing (NLP) for adaptive systems. Methods: Theoretical analysis, machine learning modeling, and testing. A chatbot was developed using Python, incorporating NLP modules (BERT), data analysis (Pandas, scikit-learn), and adaptation (K-Means), integrated with Telegram and OpenWeatherMap. It achieves 95% query processing accuracy, 4.2/5 usability, and a 1.5-second response time. Scientific Novelty: Integration of NLP and clustering for personalized solutions in agribusiness. Practical Significance: Optimization of sowing, irrigation, and risk reduction. Future Prospects: Integration of WeatherAPI, voice input, and an agronomic database.
Development of an Adaptive Chatbot for Analyzing Meteorological Data and Supporting Decision-Making in Agribusiness
Керівник: Мартиненко Артем Анатолійович, викладач кафедри інтелектуальних програмних систем і технологій
Keywords: TECHNOLOGY::Information technology::Computer science::Computer science; чат-бот; метеорологічні дані; агробізнес; штучний інтелект; NLP; кластеризація; TELEGRAM; PYTHON; chatbot; meteorological data; agribusiness; artificial intelligence; clustering